2019
DOI: 10.7897/2230-8407.100237
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Medicinal Plants: A Review

Abstract: Diabetes is a metabolic disorder which is mainly characterized by hyperglycaemia and arises by the defects in insulin secretion or insulin action or both. It is categorized into two types, type-I and type-II diabetes. The risk factors that are responsible for diabetes are genetic factor, obesity, hypertension etc. Conventionally many drugs are used for the treatment of diabetes such as biguanides, sulfonylureas, meglitinides etc. But the desired effective treatment is still not to be achieved. So researches ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…It's used as an antiaging, anti-amnesiac, antiinflammatory, anti-bacterial, anti-cancer, antifungal, antiviral, anti-venom, anti-ulcerogenic, tangy, etc. Shikha Mehta et al reported that the waterless extract of the seeds of the plant showed definite hypoglycaemic activity in streptozotocinconvinced type-II diabetic rats at the dose of 300 mg/ kg66 43 .…”
Section: Phyllanthus Emblica (Amla)mentioning
confidence: 99%
“…It's used as an antiaging, anti-amnesiac, antiinflammatory, anti-bacterial, anti-cancer, antifungal, antiviral, anti-venom, anti-ulcerogenic, tangy, etc. Shikha Mehta et al reported that the waterless extract of the seeds of the plant showed definite hypoglycaemic activity in streptozotocinconvinced type-II diabetic rats at the dose of 300 mg/ kg66 43 .…”
Section: Phyllanthus Emblica (Amla)mentioning
confidence: 99%
“…Plant-based preparations are the major fundamental player in the world of medications because of their ease of availability, low cost, and low side effects 4 . Many plants contain various bioactive compounds with significant pharmacological benefits but no/minimal harmful side effects 4,7 . Several presently available drugs originate actively or passively from plants, which have been good sources of traditional medicine and are well known for their folklore use since long ago 4,8,9 .…”
mentioning
confidence: 99%
“…Chronic hyperglycemia develops in people living with long-term diabetes. Untreated chronic hyperglycemia leads to the development of diabetic complications (Mukhopadhyay et al, 2019).…”
Section: Diabetes Complicationsmentioning
confidence: 99%